Shear wave elastography findings in Immunoglobulin A Nephropathy patients: is it more specific and sensitive for interstitial fibrosis or interstitial fibrosis/tubular atrophy?. Issue 1 (1st January 2020) - Turgutalp, Kenan; Balcı, Yüksel; Özer, Caner; Bardak, Simge; Gürses, İclal and Karabulut, Yasemin and Helvacı, İlter and Dölarslan, Esra and Demir, Serap and Kıykım, Ahmet
Abstract: Background: Prediction of prognosis in Immunoglobulin A Nephropathy (IgAN) and taking appropriate precautions may reduce annual incidence of chronic kidney disease. This may be possible by close follow-up for the development and progression of interstitial fibrosis (IF) or interstitial fibrosis/tubular atrophy (IFTA) in IgAN patients. Aim: To investigate whether Young's elastic modulus (YM) which measured shear wave elastography (SWE) might be used for follow-up of IF or IFTA in IgAN patients. Methods: Prospective study was approved by Human Research Ethics Committee. Group 1 consisted of patients with IgAN. Group 2 consisted of healthy control participants. Young's elastic modulus which is a value of stiffness along with longitudinal stiffness was used to evaluate tissue elasticity. Specificity, sensitivity, positive predictive value (PPV) of YM for the presence of IF and IFTA were evaluated. Results: Group 1 consisted of 30 participants, and group 2 consisted of 32 participants. Sensitivity and specificity of SWE to diagnose presence of IF for YM > 15 kPa were 89% and 90%, respectively. PPV among the ones whom IF was diagnosed by YM >15 kPa was 91%. Sensitivity and specificity of SWE to diagnose presence of IFTA for YM > 15 were 65% and 51%, respectively. PPV among the ones whom IFTA was diagnosed by YM >15 kPa was 78.1%. Conclusions: YM which measured SWE is highly specific and sensitive in the diagnosis of IF, but not for IFTA in IgAN patients. Therefore, progression for IF in IgAN may be followed by SWE.